Cordyceps Improves Obesity and its Related Inflammation via Modulation of Enterococcus cecorum Abundance and Bile Acid Metabolism - Wu, G. D.; Pan, A.; Zhang, X.; Cai, Y. Y.; Wang, Q.; Huang, F. Q.; Liu, Q.
Dysbiotic gut microbiota has been identified as a primary mediator of inherent inflammation that underlies the pathogenesis of obesity. Cordyceps comprises the larval body and the stroma of Cordyceps sinensis (BerK.)Sacc. parasiting on Hepialidae larvae of moths (H. pialusoberthur)with potent metabolic regulation functions. The underlying anti-obesity mechanisms, however, remain largely unknown. Here, we demonstrate that the water extract of Cordyceps attenuates glucose and lipid metabolism disorders and its associated inflammation in high-fat diet (HFD)-fed mice. 16S rRNA gene sequencing and microbiomic analysis showed that Cordyceps reduced the amounts of Enterococcus cecorum, a bile-salt hydrolase-producing microbe to regulate the metabolism of bile acids in the gut. Importantly, E. cecorum transplantation or liver-specific knockdown of farnesoid X receptor (FXR), a bile acid receptor, diminished the protective effect of Cordyceps against HFD-induced obesity. Together, our results shed light on the mechanisms that underlie the glucose- and lipid-lowering effects of Cordyceps and suggest that targeting intestinal E. cecorum or hepatic FXR are potential anti-obesity and anti-inflammation therapeutic avenues.
Keywords: BILE ACIDS; CORDYCEPS SINENSIS; ENTEROCOCCUS CECORUM; FXR; OBESITY